The surgical strategy for eosinophilic granuloma of the pediatric cervical spine complicated with neurologic deficit and/or spinal instability. Issue 1 (December 2016) - Zhong, Nanzhe; Xu, Wei; Meng, Tong; Yang, Xinghai; Yan, Wangjun; Xiao, Jianru
Abstract Background Various therapeutic approaches have been proposed for the treatment of pediatric patients with eosinophilic granuloma (EG) of the cervical spine. Our aim was to discuss and present our experience with the individualized surgical intervention of pediatric cervical EG complicated with neurologic deficits and/or spinal instability. Methods We retrospectively analyzed the clinical data of 19 children who were diagnosed with cervical EG comor spinal/or spinal instability (evaluated by the Spinal Instability Neoplastic Score, SINS ≥ 7) and treated surgically in our institution. Results Lesions involved C1–2 in 7 patients and C3–7 in 12 patients. Anterior tumor resection combined with posterior pedicle screw fixation, anterior approach of excision and instrumentation, and posterior tumor resection combined with pedicle screws instrumentation were selected according to the different locations of tumors. Frankel scale and Oucher scale improved significantly after surgery. There was no morphologic alteration of the neck at follow-up. Conclusions Surgery can significantly improve the neurologic status and symptoms. Surgical decision-making must be individually tailored to minimize the influence of surgery on spine growth.